Headache and Status Epilepticus in the Postpartum Period; Posterior Reversible Encephalopathy Syndrome or Cerebral Venous Thrombosis?. (24th April 2013) - Zis, Panagiotis; Tavernarakis, Antonios
Abstract : We report a case of a young woman, with a history of a miscarriage and a molar pregnancy, who developed headache and status epilepticus in postpartum day three. Posterior reversible encephalopathy syndrome (PRES) and cerebral venous and sinus thrombosis (CVST) can present with identical clinical picture; however, the imaging findings can help the clinician to make the correct diagnosis and initiate the appropriate treatment. Both PRES and CVST are medical emergencies and fully reversible entities especially when treatment initiation is immediate.